Why Are Households Willing to Pay for Renewable Energy? Lessons From Romania - Maxim, Alexandru; Jijie, Dumitru-Tudor; Roman, Teodora (Frontiers in Environmental Science, 2022)
Renewable energy is seen as a key tool in addressing the dual issue of increasing energy demand and climate change mitigation. In the current geopolitical climate, it may also play a key long-term role in increasing energy security. In order to reach the ambitious green energy targets set for each European Union member state public support for fiscal and other support mechanisms is required. The purpose of this paper is to determine to what extent the Romanian public is willing to make financial sacrifices for further development of renewable energy. We also explore what lifestyle and socio-demographic factors influence willingness to pay. We applied a discrete choice experiment on a sample of 602 households from the populous North-East region of Romania. Our results show that the creation of new jobs and the increase of the national energy independence, followed by the reduction of pollution are societal benefits that would convince households to pay a premium in order to support renewable energy development. Increased local budgets for rural communities resulting from the taxation of new energy companies is not one of the desired outcomes of green energy development. The study is useful in the design of adequate fiscal and renewable support policies and serves companies by identifying willingness-to-pay influence factors, as well as by demonstrating a market segmentation procedure.